From Persecution to Detention: A reflection on the non-application of Article 31(1) of the 1951 Refugee Convention on asylum seekers in Zambia - Longwe, Abel (Department of Public Law, 2021)
Despite Zambia's ratification of several of international and regional human rights instruments, the country's domestic legislation frustrates its international obligations in so far as protection of asylum seekers human rights is concerned. Principally there are two main pieces of legislation which create this ‘quagmire,' but also make provision for the entry and exit of persons in Zambia, these are the Immigration and Deportation Act No. 18 of 2010 (hereinafter referred to as the Immigration Act) and the Refugees Act No. 1 of 2017 (hereinafter the Refugees Act). Although these two pieces of legislation apply to different types of migrants, there is a predisposition on the part of the authorities of enforcing immigration laws and not refugee laws on asylum seekers especially those found unlawfully present in country. This is in contravention of the non-penalisation clause under the 1951 Convention Relating to the Status of Refugees (hereinafter the 1951 Refugee Convention), which creates a dilemma for asylum seekers. Zambia has an international obligation to receive and not to expel asylum seekers present within its territory irrespective of their mode of entry, this responsibility emanates from Article 31(1) and Article 33(2) 1951 Refugee Convention. However, the misapplication of the Immigration Act on asylum seekers conflicts with this obligation.